Proposta de instrumentos para a realização de análise ambiental inicial em ETEs à luz da NBR ISO 14001:2004: o caso da ETE-Monjolinho, São Carlos-SP - Fajardo, Poliana Arruda (2014)
The construction of wastewater collection systems and the implantation of Wastewater Treatment Plants (WWTPs) are not guarantees that environmental and public health problems on the wastewater are fully resolved, because the WWTPs require inputs to function and generate wastes and tailings during their operation and may, thus, also become sources of environmental pollution and cause damage to the population. Besides the Environmental Licensing, which includes the Preliminary License, Installation License and Operating License, and the Environmental Impact Assessment (EIA), two management tools can assist the management of WWTPs in this way: the NBR ISO 14001:2004, for the implementation of an Environmental Management System (EMS), and NBR ISO 14004:2005, which recommends conducting an Initial Environmental Review before installing the system, although does not have tools that can be used for this purpose. Thus, the general objective of this work was to develop tools to aid in conducting this Review in WWTPs, having as object of study WWTP-Monjolinho - São Carlos-SP, which wastewater treatment consists of: preliminary treatment, biological treatment with UASB reactors, dissolved-air flotation - preceded by flocculation with metallic coagulants and polymers -, ultraviolet (UV) radiation disinfection and postaeration of treated wastewater by cascade aeration before its throwing to Monjolinho river. The research was performed in four stages. At first, it was performed theoretical background; in the second, the knowledge of the object of study; in the third, the tools of Initial Environmental Review were developed and applied to WWTP-Monjolinho; and in the fourth stage there was the presentation and discussion of the results, as well as the research finals considerations. Eight tools and also the results of their application to WWTP-Monjolinho were obtained. It is considered that, through the tools developed in this work, the WWTPs, as WWTP-Monjolinho, can guide themselves more appropriately in search of the EMS installation and improve their activities, in order to more adequately meets increasing aspirations from society for a better quality of life and environmental protection and conservation.